2022
DOI: 10.3390/ma15062232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Sintering Densification of Multi-Scale Silver Layer

Abstract: Based on molecular dynamics (MD), in this study, a model was established to simulate the initial coating morphology of silver paste by using a random algorithm, and the effects of different sizes of particles on sintering porosity were also analyzed. The MD result reveals that compared with the sintering process using large-scale silver particles, the sintering process using multi-scale silver particles would enhance the densification under the same sintering conditions, which authenticates the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Gu et al [11] simulated the sintering process of silver particles under four particle sizes and described the four sintering mechanisms. Liang et al [12] simulated the mixed sintering of silver particles of different sizes, and compared it with the sintering of silver particles of the same size, they found that after sintering, silver particles of different sizes had lower porosity and smaller pores, and also found that small particles can be filled between large particles to increase the width of the knotted neck, and "reduce" the distance of the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [11] simulated the sintering process of silver particles under four particle sizes and described the four sintering mechanisms. Liang et al [12] simulated the mixed sintering of silver particles of different sizes, and compared it with the sintering of silver particles of the same size, they found that after sintering, silver particles of different sizes had lower porosity and smaller pores, and also found that small particles can be filled between large particles to increase the width of the knotted neck, and "reduce" the distance of the neck.…”
Section: Introductionmentioning
confidence: 99%